Dermatophyte Fungi Causing Tinea Unguium in Toenails of Builders in Bangkalan: Jamur Dermatophyte Penyebab Tinea Unguium pada Kuku Jari Kaki Pekerja Konstruksi di Bangkalan - Aini, Aqiliyanti Nur; Rini, Chylen Setiyo; Mushlih, Miftahul; Puspitasari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Tinea unguium is a nail plate infection commonly caused by dermatophyte fungi, frequently affecting individuals exposed to moist and contaminated environments. Specific Background: Builders are one of the occupational groups at high risk due to their constant contact with damp, dirty, and unhygienic surroundings. Knowledge Gap: Despite its prevalence, limited studies have focused on identifying specific dermatophyte species responsible for toenail infections among construction workers in Bangkalan, Madura. Aims: This study aimed to identify dermatophyte fungi causing Tinea unguium in the toenails of builders in Bangkalan. Results: Using a descriptive cross-sectional design with 28 purposively selected nail samples, findings revealed infections in 18 participants by Trichophyton rubrum, Trichophyton mentagrophytes, and Epidermatophyton floccosum, while 10 samples showed non-dermatophyte fungi (Aspergillus sp. and Scopulariopsis). Novelty: This research provides the first documentation of both dermatophyte and non-dermatophyte fungi associated with toenail infections among builders in this region. Implications: The findings underscore the need for occupational health awareness and preventive strategies targeting fungal nail infections among construction workers. Highlights: First identification of toenail dermatophytes in builders of Bangkalan. Found both dermatophyte and non-dermatophyte fungi species. Supports occupational health awareness for fungal infections. Keywords: Tinea Unguium, Dermatophyta, Toenails, Builders, Bangkalan